THE USE OF FLASH ANIMATION TO TEACH PRESENT CONTINOUS TENSE - Nafi’, M. Khoirun (VISION, 2014)
ABSTRACT Â Grammar is a crucial thing in a language. Peopleâs speech may not be understandableÂ if it is not uttered in good grammar. Grammatical mistakes often disturb the flow of communication. The comprehensibility of a personâ speechÂ is tightly related to the mastery of grammar. Moreover, grammar may also relate to speakerâs level of education. English language learners often think of grammar as a rather boring school subject which has little use in real life. They may have came across the concepts in learning language like France or Latin, in English composition, or the explanation of teachers as to what is god or bad grammar. The difference between English and Indonesian grammatical system and the teaching learning process which are teacher centred cause the students feel difficult to understand the grammar especially present continuous. Students get bored of learning it since the material is not conveyed in an interesting way. This paper discusses the use of flash animation in teaching present continuous tense. The discussion is based on the writer experience in implementing flash animation in his grammar teaching, the present continous tense at SMP 1 Mejobo Kudus. Â Keywords: flash anmation, grammar, present continous tense